The Role of Artificial Intelligence (AI) in Financial Risk Management - Sari, Yovita; Indrabudiman, Amir (PT FORMOSA CENDEKIA GLOBAL, 2024)
Artificial intelligence (AI) has become a major trend in the financial industry in recent years. AI offers a range of benefits for financial institutions, including improved accuracy, efficiency, effectiveness, and compliance. In financial risk management, AI is used to analyze financial data and market trends to identify and manage risks, as well as generate accurate risk reports. This research aims to explore the role of AI in financial risk management through a literature review. The findings show that AI can enhance the speed of risk detection, improve effectiveness and efficiency in risk management processes. Theoretically, AI brings a paradigm shift in technology-based risk management and contributes to the development of financial risk management theories